The way to a man's heart is through his stomach?: a mixed methods study on causal mechanisms through which cash and in-kind food transfers decreased intimate partner violence - Ana Maria Buller; Melissa Hidrobo; Amber Peterman; Lori Heise (BMC, 2016)
Abstract Background Intimate partner violence (IPV) is highly prevalent and has detrimental effects on the physical and mental health of women across the world. Despite emerging evidence on the impacts of cash transfers on intimate partner violence, the pathways through which reductions in violence occur remain under-explored. A randomised controlled trial of a cash and in-kind food transfer programme on the northern border of Ecuador showed that transfers reduced physical or sexual violence by 30 %. This mixed methods study aimed to understand the pathways that led to this reduction. Methods We conducted a mixed methods study that combined secondary analysis from a randomised controlled trial relating to the impact of a transfer programme on IPV with in-depth interviews and focus group discussions with male and female beneficiaries. A sequential analysis strategy was followed, whereby qualitative results guided the choice of variables for the quantitative analysis and qualitative insights were used to help interpret the quantitative findings. Results We found qualitative and quantitative evidence that the intervention led to reductions in IPV through three pathways operating at the couple, household and individual level: i) reduced day-to-day conflict and stress in the couple; ii) improved household well-being and happiness; and iii) increased women's decision making, self-confidence and freedom of movement. We found little evidence that any type of IPV increased as a result of the transfers. Discussion While cash and in-kind transfers can be important programmatic tools for decreasing IPV, the positive effects observed in this study seem to depend on circumstances that may not exist in all settings or programmes, such as the inclusion of a training component. Moreover, the programme built upon rather than challenged traditional gender roles by targeting women as transfer beneficiaries and framing the intervention under the umbrella of food security and nutrition - domains traditionally ascribed to women. Conclusions Transfers destined for food consumption combined with nutrition training reduced IPV among marginalised households in northern Ecuador. Evidence suggests that these reductions were realised by decreasing stress and conflict, improving household well-being, and enhancing women's decision making, self-confidence and freedom of movement. Trial registration ClinicalTrials.gov NCT02526147 . Registered 24 August 2015.